Arystoteles i Biblia pod mezoamerykańskim dachem. Chrystianizacja przez asymilację aspektów wierzeń i dziejów nahua w narracji „Historia ecclesiástica indiana” Jerónimo de Mendiety (1525-1604) - Wojtczak, Igor (Studia Europaea Gnesnensia, 2023)
The aim of this paper is to identify and define how elements of the native Mesoamerican Nahuan beliefs are described in „Historia eclesiástica indiana”, the chronicle written by Spanish Franciscan friar Jerónimo de Mendieta (1525-1604). The Catholic monk exploited numerous components of the Nahuan religious system, while this paper focuses on Mendieta’s rendering of the legendary character of Ce Acatl Topiltzin Quetzalcoatl, Toltec priest-emperor as well as on the native speeches huehuetlahtolli, delivered by Nahuan parents to their children. The ecclesiastical historian uses the aforementioned themes to unfold his own ideas and narrative about the past and colonial reality of the Nahua people. Mendieta’s writings are compared with fragments of an encyclopaedia by the Franciscan Bernardino de Sahagún (1499-1590), „Historia general de las cosas de Nueva España”, the key source to studying religion and culture of the precolonial societies in Central Mexico. The paper also draws on the accounts of other colonial authors, such as Motolinia, Olmos and Durán.